REMAINS FROM THE ALIENS IN THE NOVEL ROADSIDE PICNIC BY A. AND B. STRUGATSKY (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
Arkady and Boris Strugatsky are the most prominent and best-known Russian writers of the science fiction genre, both in the post-Soviet states and further abroad.  Their most popular and most widely translated novel is Roadside Picnic [Piknik na obochine].  It was first published serially in 1971 in the Leningrad journal Avrora. It became more popular after the famous film adaptation Stalker by Andrey Tarkovsky, realized in 1979 and the 1986 Chernobyl disaster when specific "Zone" was created, so the Strugatsky brothers become prophets Zone of a kind. Afterwards, the terms – "Zone" and "Stalker" (a brave and criminal man who goes to Zone to find specific artifacts there in order to sell them to collectors and others) – became known all over the World. In this article the author writes about the theme of the first contact in the genre of science fiction on the example of this novel where there is no communication between human and alien civilization. However, the Visitors from outer space left artifacts which have great influence on people on Earth, especially in places near the Zone. For the purpose of this article English translation of the novel and reviews by Russian and foreign authors, letters and work diaries by Strugatsky's have been used.Keywords: Strugatsky brothers; Science fiction; Aliens Zone; First contact.